2017
DOI: 10.5194/acp-17-3067-2017
|View full text |Cite
|
Sign up to set email alerts
|

30-year lidar observations of the stratospheric aerosol layer state over Tomsk (Western Siberia, Russia)

Abstract: Abstract. There are only four lidar stations in the world which have almost continuously performed observations of the stratospheric aerosol layer (SAL) state over the last 30 years. The longest time series of the SAL lidar measurements have been accumulated at the Mauna Loa Observatory (Hawaii) since 1973, the NASA Langley Research Center (Hampton, Virginia) since 1974, and Garmisch-Partenkirchen (Germany) since 1976. The fourth lidar station we present started to perform routine observations of the SAL param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Figure a compares to a newly available lidar record from Tomsk, Siberia (Zuev et al, ). While the tropopause altitude is generally 11–13 km, the lidar backscatter was integrated between 15 and 30 km.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Figure a compares to a newly available lidar record from Tomsk, Siberia (Zuev et al, ). While the tropopause altitude is generally 11–13 km, the lidar backscatter was integrated between 15 and 30 km.…”
Section: Resultssupporting
confidence: 85%
“…Aerosol optical depth (AOD) measured by lidars at three locations (black circles) are compared to calculated 5 day average AOD above the tropopause in corresponding model columns from our SDVOLC (red dots), FRVOLC (ensemble average, blue dots), and SCVOLC (orange dots) simulations. Observations are (a) integrated backscatter from 15–30 km measured in Tomsk, Siberia (Zuev et al, ), converted to AOD using a lidar ratio of 50; (b) AOD above the tropopause measured in Geestacht, Germany (Ansmann et al, ); and (c) AOD above the tropopause measured in Mauna Loa, Hawaii (Hofmann et al, ; Ridley et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Based upon satellite observations, showed that the decadal increase in stratospheric aerosol loadings since 2002 can be attributed to a series of moderate volcanic eruptions. As reported by Kremser et al (2016), this decadal trend was also obtained from lidar (Hofmann et al, 2009;Trickl et al, 2013;Zuev et al, 2017) and ground-based sun photometer observations (Ridley et al, 2014). Three moderate volcanic eruptions occurred in the 2002-2012 period are ranked in the top 10 of the most influential events on the stratospheric aerosol burden, including (1) the Kasatochi eruption (52.2 • N, 175.5 • W; Alaska) in 2008, which injected 1.5-2.5 Tg of SO 2 into the upper troposphere and lower stratosphere (UTLS; Kravitz et al, 2010;Krotkov et al, 2010), (2) the Sarychev eruption in June 2009 (48.1 • N, 153.2 • E; the Kuril Islands), which released 0.9 Tg of SO 2 into the UTLS (Clarisse et al, 2012;Kravitz et al, 2011;Jégou et al, 2013), and (3) the Nabro eruption (13.4 • N, 41.7 • E; Eritrea) in June 2011, which emitted 1.3 Tg of SO 2 into the UTLS Sawamura et al;.…”
supporting
confidence: 81%
“…This allows us to derive the particle backscatter coefficient (β p ) and the scattering ratio (SR, e.g. Zuev et al, 2017), which is the primary, ALC-derived parameter used in this work to quantify the aerosol load. It is defined as…”
Section: Study Region and Experimental Setupmentioning
confidence: 99%